The History and Contribution of Philosophy in Islamic Thought - Robby Habiba Abror (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2020)
The purpose of this study was to provide information about the Islamic philosophical discourse that contributed to the world of Islamic education in particular and Islamic intellectual property in general. This research used a qualitative method with a literature review in collecting material objects. This research found that the Islamic philosophy originated from the Greek philosophy, especially the Peripatetic tradition and its Neo-Platonism style, but were not imitations of it. The Islamic philosophy that grew from a distinctive Islamic culture gave birth to authentic intellectual creativity products in the history of Islamic thought and civilization. The Islamic philosophy was actually a mixture of Aristotelianism and Neo-Platonism since Greek works had been translated into Arabic and spread across the Arabian Peninsula during the Abbasid Dynasty in the Islamic empire. However, the Islamic philosophy could harmonize Aristotle and Plato; and successfully reconciled reasons and revelations. It can be concluded that the Islamic philosophy was not stagnant, but was dynamic and always actual in producing philosophical ideas that could provide solutions for this era.